KOMPETENSI PEDAGOGIK GURU PAI DALAM MENANAMKAN AJARAN ISLAM PADA SISWA KELAS VIII (Studi Kasus di SMP Negeri I Sindang Kelingi) - Siswanto siswanto; Eli Susanti (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2018)
Based on preliminary field observation that the pedagogic competence of teachers in managing learning in SMP Negeri 01 Sindang Kelingi is still conventional, the time used is very short, the lack of learning media, then also there is a symptom that the lack of teacher competence in managing learning or low knowledge of teachers. This study aims to determine the pedagogic competence of PAI teachers in inculcating the teachings of Islam in the students in Junior High School I Sindang Kelingi especially in terms of aqidah and akhlak. To find out what factors are inhibiting PAI teachers in instilling Islamic teachings in students of SMP Negeri I Sindang Especially in terms of aqidah and morals. This research is a field research (fild reserch) using qualitative descriptive research. The subjects of the study were all PAI SMPN I Sindang Kelingi teachers, 3 teachers, other teachers, and some grade VIII students to find out pedagogic competence of teachers. Data collection techniques are by observation, interview, documentation, and triangulation. The data analysis techniques used are with data reduction, data presentation, and verification or conclusion. The result of the research shows that pedagogic competence of PAI teachers in instilling Islamic teachings in the students of SMP Negeri I Sindang Kelingi is good enough, from understanding teacher insight, understanding to learners, teacher ability in designing and implementing learning, teacher ability in evaluating learning result,and the ability of teachers in developing the potential of students to actualize themselves, but not maximized. In instilling the teachings of Islam on the students, there are several factors inhibiting pedagogic competence of teachers in instilling Islamic teachings on the students such as no seriousness and lack of interest of students in learning and the time used is very short so inefficient, poor communication of students and teachers so that learning is not communicative, and lack of learning media.